HUBUNGAN ARUS, KECEPATAN DAN KEPADATAN LALU LINTAS PADA RUAS JALAN MAJAPAHIT KOTA MATARAM - Murtadinata, Agista; Wahyuningsih, Titik; Efendy, Anwar (Politeknik Negeri Semarang, 2024)
Majapahit Road is one of the provincial roads which is included in the collector road class with 4/2 D lane type in Mataram City. This road is a road that connects activity centers which causes the traffic volume to increase, resulting in reduced road performance. In this research, the relationship between the three main components of traffic flow, namely volume (Q), speed (V) and density (D), is analyzed in three methods, namely the Greenshield, Greenberg and Underwood models. From the results of research and analysis of traffic flow data, the density during traffic jams (Dj) was obtained from each model, where the Greenshield Model got a value between 271,375 ”“ 604,118 pcu/km, the Greenberg Model got a value between 164,001 ”“ 3899,011 pcu/km, The Underwood model gets values between 224,210 ”“ 504,674 pcu/km. From the summary of the analysis results, the Greenshield Model gets a capacity value between 3054,215 ”“ 5844,222 pcu/hour, the Greenberg Model gets a capacity value between 436,546 ”“ 7867,297 pcu/hour and the Underwood Model gets a capacity value between 3778,396 ”“ 7297 ,475 pcu/hour.